Biogenic nanosilver bearing antimicrobial and antibiofilm activities and its potential for application in agriculture and industry - Trzcińska-Wencel, Joanna; Wypij, Magdalena; Rai, Mahendra; Golińska, Patrycja (Frontiers in Microbiology, 2023)
Introduction Due to the increasing resistance of bacteria and fungi to antimicrobials, it is necessary to search for effective alternatives to prevent and treat pathogens causing diseases in humans, animals, and plants. In this context, the mycosynthesized silver nanoparticles (AgNPs) are considered as a potential tool to combat such pathogenic microorganisms. Methods AgNPs were synthesized from Fusarium culmorum strain JTW1 and characterized by Transmission Electron Microscopy (TEM), X-ray diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, Nanoparticle Tracking Analysis (NTA), Dynamic Light Scattering (DLS) and Zeta potential measurement. The minimum inhibitory (MIC) and biocidal concentrations (MBC) were determined against 13 bacterial strains. Moreover, the combined effect of AgNPs with antibiotics (streptomycin, kanamycin, ampicillin, tetracycline) was also studied by determining the Fractional Inhibitory Concentration (FIC) index. The anti-biofilm activity was examined by crystal violet and fluorescein diacetate (FDA) assays. Furthermore, antifungal activity of AgNPs was evaluated against a panel of phytopathogenic fungi viz., Botrytis, Colletotrichum, Fusarium, Phoma, Sclerotinia, and an oomycete pathogen Phytophthora by agar well-diffusion and micro-broth dilution method to evaluate the minimal AgNPs concentrations that inhibit fungal spore germination. Results Fungi-mediated synthesis resulted in the formation of small (15.56 ± 9.22 nm), spherical and stable (zeta potential of – 38.43 mV) AgNPs with good crystallinity. The results of FTIR spectroscopy indicated the presence of various functional groups, namely hydroxyl, amino, and carboxyl ones, from the biomolecules on the surface of AgNPs. The AgNPs showed antimicrobial and antibiofilm formation activities against Gram-positive and Gram-negative bacteria. The values of MIC and MBC ranged between 16–64 and 32–512 μg mL−1, respectively. The enhanced effect of AgNPs in combination with antibiotics was confirmed against human pathogens. The highest synergistic effect (FIC = 0.0625) was demonstrated by the combination of AgNPs with streptomycin against two strains of Escherichia coli (ATCC 25922 and ATCC 8739), followed by Klebsiella pneumoniae and Pseudomonas aeruginosa (FIC = 0.125). Enhanced effects of AgNPs with ampicillin were also shown against Staphylococcus aureus ATCC 25923 (FIC = 0.125) and P. aeruginosa (FIC = 0.25), as well as kanamycin against S. aureus ATCC 6538 (FIC = 0.25). The crystal violet assay revealed that the lowest concentration of AgNPs (0.125 μg mL−1) reduced the development of biofilms of Listeria monocytogenes and Salmonella enterica, while the maximum resistance was shown by Salmonella infantis, its biofilm was reduced after exposure to a concentration of 512 μg mL−1. A high inhibitory effect on the activity of bacterial hydrolases was observed by the FDA assay. AgNPs at a concentration of 0.125 μg mL−1 reduced the hydrolytic activity of all biofilms formed by the tested pathogens, except E. coli ATCC 25922, P. aeruginosa, and Pectobacterium carotovorum (efficient concentration was 2-fold higher, at 0.25 μg mL−1), while the hydrolytic activity of E. coli ATCC 8739, Salmonella infantis and S. aureus ATCC 6538 was suppressed after treatment with AgNPs at concentrations of 0.5, 2 and 8 μg mL−1, respectively. Moreover, AgNPs inhibited fungal growth and spore germination of Botrytis cinerea, Phoma lingam, and Sclerotinia sclerotiorum. MIC and MFC values of AgNPs against spores of these fungal strains were determined at 64, 256, and 32 μg mL−1, and zones of growth inhibition were 4.93, 9.54, and 3.41 mm, respectively. Discussion Fusarium culmorum strain JTW1 was found to be an eco-friendly biological system for an easy, efficient and inexpensive synthesis of AgNPs. In our study, the mycosynthesised AgNPs demonstrated remarkable antimicrobial (antibacterial and antifungal) and antibiofilm activities against a wide range of human and plant pathogenic bacteria and fungi singly and in combination with antibiotics. These AgNPs could be applied in medicine, agriculture, and food industry to control such pathogens that cause numerous human diseases and crop losses. However, before using them extensive animal studies are required to evaluate the toxicity, if any.